Pengaruh Organizational Citizenship Behavior dan Lingkungan Kerja terhadap Kinerja Karyawan melalui Kepuasan Kerja sebagai Variable Intervening PT. Inhutaniv - Firman Pratomo Putro (Jurnal Syntax Admiration, 2024)
This research was conducted to understand how “Organizational Citizenship Behavior and work environment affect employee performance with job satisfaction as a mediating variable at PT Inhutani V”. This study used saturated sampling technique, where the entire population of 138 people became respondents. Data were collected through questionnaires, then analyzed using the SEM method processed with the Smart PLS 4.0 application. The findings of the analysis tested on employee performance at PT Inhutani V show that Organizational Citizenship Behavior (OCB) and the work environment are proven to have a positive and significant effect. In addition, it was also found that the factor of employee job satisfaction had a positive and significant relationship with their performance. Furthermore, OCB plays a positive and significant role in influencing employee job satisfaction, as well as the work environment. Furthermore, OCB contributes positively and significantly to employee performance when job satisfaction acts as a mediating variable. Meanwhile, although the effect of work environment on employee performance through mediating job satisfaction is positive, the effect is not significant.